Gestión del talento y satisfacción de los usuarios del albergue Yanayacu River Lodge de Iquitos periodo setiembre 2023 - Najarro Rueda, Nick Gioovanni (2025)
The general objective of the research developed was to determine the relationship between Talent Management and the Satisfaction of the users of the Yanayacu River Lodge in Iquitos, September 2023, the work is basic type, with a quantitative approach, correlational level and non-experimental design. It was determined that there is a significant positive correlation between processes for selecting people and user satisfaction with a Pearson value equal to 0.552. It was also determined that there is a significant positive relationship between the processes for rewarding people and user satisfaction with a Pearson value of 0.701 and finally there is a significant positive relationship between the processes to develop people and User Satisfaction with a Pearson correlation value equal to 0.993 and concluded that there is a significant positive relationship between Talent Management and User Satisfaction. users with a Pearson correlation value equal to 0,842.